Clinico-epidemiological study on canine toxicosis in Effurun/Warri Municipality region of Delta State, Nigeria (Journal of Advanced Veterinary and Animal Research, 2015)
The purpose of this study was to providefundamental information on both the commontoxicants and poisoning episodes in dogs withinEffurun/Warri municipality region of Delta State ofNigeria from 2011 to 2014. The collected data weregrouped according to age, sex, breed, year ofoccurrence, and toxicant type. The study revealedthat a total of 76 dogs comprising 12 breeds werepoisoned by several toxicants such as pesticides(69%; n=52/76), household products (12%; n=9/76),foodpoisons (9%; n=7/76), and snakebiteenvenomation (3%; n=2/76). Mixed breeds (29%;n=22/76), Alsatian (25%; n=19/76), Rottweiler (16%;n=12/76) and indigenous breed (7%; n=5/76) rankedthe topmost breeds accounted for most poisonemergencies with humanrelated factorsincriminated. This study provides usefulinformation on episodes of poisoning in dogs inthe studied region. The knowledge of agentsinvolved can help veterinarians for accuratediagnosis, and pet owners to cautiously protecttheir pets from potentially poisonous substances.http://dx.doi.org/10.5455/javar.2015.b91